NEW OPTIONS FOR SOLAR DRYERS BASED ON ALTERNATIVE ENERGY SOURCES (American Journal of Pedagogical and Educational Research, 2023)
This article analyzes the optimal options for making solar dryers and the optimal options for different structured solar dryers and selects an economically efficient option.